Implementasi Program Zero Waste pada Masyarakat Kota Mataram - Febrian Evayanti; Bagdawansyah Alqadry; M. Ismail; Muh. Zubair (MANAZHIM, 2022)
NTB Zero Waste program is one of the superior programs of the NTB government. The research purposes are to find out how to implement the program in the Mataram citizen, the supporting factors, and inhibiting factors of this zero-waste program. This research used a qualitative descriptive method, in which the author only describes the problem as it is or by the reality that occurs in the object of research. The research techniques used in this study were interview, observation, documentation, and questionnaire or survey. The data analysis technique by Milles and Huberman was used in this research. The technique has three stages; data reduction, data display, and conclusion drawing. The results of this research show that many people have heard and know about the word zero waste, but a only few of them know that the NTB government has a zero-waste program. The citizen feels that the government still lack effort in socializing this program thus many people still do not know. The supporting factors in the implementation of this zero waste program are government support, budget funds, and staff (HR). While the inhibiting factors are public awareness and infrastructure.